PENGGUNAAN ANKLE FOOT ORTHOSIS (AFO) TERHADAP KESEIMBANGAN FUNGSIONAL PADA ANAK PENDERITA CEREBRAL PALSY - Hisyam Syafi'ie; Fadhila Firmanurulita (Medical Journal of Nusantara, 2024)
Children with cerebral palsy will experience problems with their movements. Cerebral palsy affects muscles and a person's ability to control them. One of the disorders that occur in children with CP is disturbances in walking balance, which ultimately results in disturbances in walking motor skills, so children experience disturbances in daily living (ADL) activities in their daily lives. This research aims to determine the effect of using Anke Foot Orthosis on children's functional balance. Cerebral Palsy. Method: This type of research uses a Quasy Experiment with a pretest-posttest with a control group design. The total sample for this study was 10 respondents. Data collection was carried out using observation sheets. Analysis of this research data using univariate and bivariate analysis with Wilcoxon. Results: The influence of using Anke Foot Orthosis on the functional balance of Cerebral Palsy children, data taken before and after treatment with a value > 0.05. The conclusion is that there is no significant effect between using Anke Foot Orthosis and functional balance in children with cerebral palsy.